Kingdom of Lesotho : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2018)
This Selected Issues paper provides further background on the macrofinancial sector analysis that informed Lesotho's 2017 Article IV consultation. Lesotho's financial sector is small, concentrated, and lacks financial inclusion, although mobile banking services and financial cooperatives offer some encouraging potential. Lesotho's most important vulnerabilities are exposure to developments in South Africa and dependence on revenues from the Southern African Customs Union (SACU). Shocks to SACU revenues can become a source of systemic risk by affecting the fiscal position and the balance of payments. The financial system will be affected by both channels, with substantial implications if the shock is permanent. This paper focuses on two potential consequences of a severe SACU revenue shock for the financial system: A decline in reserves that may threaten the sustainability of the hard currency peg with the South African rand, and the impact of a forced fiscal consolidation on household income and the quality of credit to households, affecting both bank and nonbank lenders. It turns out that financial shallowness and lack of inclusion may be a defining feature of the formal banking system; thereby raising questions about potential trade-offs between inclusiveness and financial stability.